TO PREDICT PREDICTORS THAT DETERMINE THE LEVEL OF PROFESSIONAL TRAINING OF TEACHER EDUCATION STUDENTS - Saodat Mamasaxatovna Yuldasheva (Western European Studies, 2024)
The content of this article is aimed at predicting predictors that determine the level of professional training of students in teacher education. At the same time, it was determined that the constant value for predicting the degree of ability of students at a number of universities to improve the predictors that need to be formed into a teacher-trainer in the process of pedagogical professional training. The results of the study were analyzed psychologically. The successful development of skills necessary for professional activity, professional maturity is perceived as a result of abilities and a positive relationship between personal qualities. In the process of professional maturity, the formation of professional abilities is ensured by the totality of a person’s individual characteristics. The transition to professional activity is a stepby-step process, and the transition from education to independent professional activity is an important aspect of every person’s life. The professional orientation of a teacher’s personality is often firmly connected with his personal development and manifests itself in a harmonious state. To assess his professional maturity, it is necessary to highlight a number of aspects of his activity. The growth of social demands determines the place of the profession and specialist in the life of society. For this reason, it is necessary today to use the terms “significant” and “obsolete profession”. The same point of view and worldview continue to guide young people in choosing a profession. For our research, taking these requirements into account serves to identify the causes of imbalance in career choice and develop recommendations for its prevention
Keywords: pedagogical direction; student; professional training; communication